2015
DOI: 10.1021/jacs.5b05033
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Cyclopropenimine Superbases: Direct Neutral Brønsted Base Catalyzed Michael Reactions with α-Aryl Esters

Abstract: The synthesis and characterization of six new classes of higher-order superbases, including five that incorporate cyclopropenimine functionality, has been achieved. We propose a nomenclature that designates these as the CG2, GC2, PC3, PC1, C3, and GP2 classes of superbases. The pKBH+ values were measured to be between 29.0 and 35.6 in acetonitrile. Linear correlations of ten superbase basicities vs. that of their substituents demonstrated the insulating effect of the cyclopropenimine core. The molecular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 62 publications
0
46
0
1
Order By: Relevance
“…Treatment of PCl 3 with five equivalents of (NI i Pr)H in THF at 0 °C resulted in the formation of the protonated phosphine [HP(NI i Pr) 3 ] + Cl − ( 3 ⋅HCl) and the guanidinium salt [(NI i Pr)H 2 ] + Cl − as evidenced by NMR spectroscopy (see Figure S7 and S8 in the Supporting Information). Surprisingly, an excess of (NI i Pr)H [p K BH + (MeCN)=24.5] does not deprotonate the phosphonium salt indicating the superbasic character of phosphine 3 . Deprotonation with KO t Bu affords a mixture of 3 ⋅ n (KCl) [ δ ( 31 P)=85.1 ppm] and (NI i Pr)H from which the guanidine was recovered in 95 % yield by sublimation.…”
Section: Figurementioning
confidence: 99%
“…Treatment of PCl 3 with five equivalents of (NI i Pr)H in THF at 0 °C resulted in the formation of the protonated phosphine [HP(NI i Pr) 3 ] + Cl − ( 3 ⋅HCl) and the guanidinium salt [(NI i Pr)H 2 ] + Cl − as evidenced by NMR spectroscopy (see Figure S7 and S8 in the Supporting Information). Surprisingly, an excess of (NI i Pr)H [p K BH + (MeCN)=24.5] does not deprotonate the phosphonium salt indicating the superbasic character of phosphine 3 . Deprotonation with KO t Bu affords a mixture of 3 ⋅ n (KCl) [ δ ( 31 P)=85.1 ppm] and (NI i Pr)H from which the guanidine was recovered in 95 % yield by sublimation.…”
Section: Figurementioning
confidence: 99%
“…[54] Thei ncreased basicity of these high-order superbases allows the activation of poorly reactive nucleophiles,f or example the N-position of indoles Besides the application of superbases in Michael and Mannich reactions,W aymouth and co-workers recently showed that cyclopropenimines 194-196 were capable of effectively initiating polymerization reactions of lactides with and without additional alcohols as co-initiators. [54] Thei ncreased basicity of these high-order superbases allows the activation of poorly reactive nucleophiles,f or example the N-position of indoles Besides the application of superbases in Michael and Mannich reactions,W aymouth and co-workers recently showed that cyclopropenimines 194-196 were capable of effectively initiating polymerization reactions of lactides with and without additional alcohols as co-initiators.…”
Section: Asymmetric Synthesis With Cyclopropenium Ionsmentioning
confidence: 99%
“…In 2015 Nacsa and Lambert extended their studies on cyclopropenimines through the design and synthesis of several higher-order cyclopropenimine-containing superbases (185-189 and 193,S cheme 25). [54] Thei ncreased basicity of these high-order superbases allows the activation of poorly reactive nucleophiles,f or example the N-position of indoles or the a-position of esters.Asregards the latter,various 2-aryl acetic acid esters 190 and electron-deficient olefins 191 have been shown to readily undergo the Michael addition reaction to afford the products 192 in excellent yields but low diastereoisomeric ratios.T his poor stereoselectivity can possibly be attributed to the absence of hydrogen bonding in the transition state (see Scheme 23).…”
Section: Asymmetric Synthesis With Cyclopropenium Ionsmentioning
confidence: 99%
“…Aromaticity can stabilize the positive charge on the superbase's conjugate acid by delocalization and the basicity increases. The number of investigations using this factor to design the superbases is scarce . Lambert et al .…”
Section: Introductionmentioning
confidence: 99%